Spent grain as a new carrier for trypsin immobilisation - Rocha, Cristina M. R. (2007)
Trypsin is a widely used enzyme for protein hydrolysis and can be used to improve functional and nutritional properties of foods. This work compares different carriers obtained from spent grains as potential candidates for trypsin immobilisation. Covalent attachment to the carriers was tested using glutaraldehyde. The efficiency of immobilisation and activity, operation and storage stability of free and immobilised enzyme on supports were determined. The amount of immobilised protein achieved was high (up to 70 %) but there was a significant loss of enzyme activity with the immobilisation of trypsin. However, when a more purified enzyme from bovine pancreas was used, activity retention was almost 50 %. Trypsin was most successfully immobilised on the supports by covalent attachment using glyoxyl-derivatives. The stability of these immobilized enzymes was close to 100%.